Prognostic Value of LC3B and p62 Expression in Small Intestinal Adenocarcinoma - Jeong-Won Kim (MDPI AG, 2021)
Autophagy, a mechanism that maintains cellular homeostasis, is involved in tumor cell growth and survival in cancer, and autophagy inhibitors have been tested clinical trials for anticancer therapy. To elucidate the clinical and prognostic implications of autophagy in small intestinal adenocarcinoma (SIAC), we assessed the expression of autophagy markers, LC3B and p62, in 171 surgically resected primary SIACs using automated quantitative analysis. Positive LC3B, p62 nuclear (p62Nu), and p62 cytoplasmic (p62Cy) expression was observed in 23 (13.5%), 52 (30.4%), and 43 (25.1%) carcinomas, respectively. LC3B+ expression was correlated with undifferentiated carcinoma (p < 0.001) and high histologic grade (p = 0.029). The combined expression of LC3B and p62Nu (LC3+/p62Nu+) was related to the older age of patients (p = 0.017), undifferentiated carcinoma (p < 0.001), and high grade (p = 0.031). LC3B+ (p = 0.006), p62Cy+ (p = 0.041), or p62Nu+ (p = 0.006) expression were associated with worse survival. In addition, SIAC patients with either LC3B+/p62Nu+ (p = 0.001) or LC3B+/p62Cy+ (p = 0.002) expression had shorter survival times. In multivariate analysis, LC3B expression remained an independent prognostic factor (p = 0.025) for overall survival. In conclusion, autophagy may play a role in the tumorigenesis of SIACs, and LC3B and p62 could be used as prognostic biomarkers and potential therapeutic targets for SIACs.